Taking on the National Board for Professional Teaching Standards: Alignment, Recognition and Representation - Frank Serafini (Arizona State University, 2015)
The National Board for Professional Teaching Standards (NBPTS) was established in 1987 to develop and operate a system of advanced certification; including a set of high and rigorous standards of accomplished teaching and an assessment system designed to measure these standards. Utilizing a qualitative, case study framework, this research project was designed to investigate the meaning perspectives associated with the NBPTS certification process from the point of view of a National Board candidate interacting with the procedures, assessments and requirements necessary to achieve certification. The study asserts the candidate focused on the alignment of her teaching to the vision of accomplished practice set forth in the NBPTS standards, the possible recognition of being NBPTS certified, and the challenges with representing teaching practices through the assessment vehicles provided in the certification process.